Photosensitive organic insulating material composition, insulating film, gate insulating film, transistor, electronic device, and method for producing transistor
By introducing chalcone compounds into photosensitive organic insulating materials, the problem of insufficient absorption of polyvinyl cinnamate during i-line exposure was solved, enabling rapid curing and efficient production.
Patent Information
- Application Number
- CN202380095627.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-11-11
AI Technical Summary
The polyvinyl cinnamate photosensitive resin material used in the prior art has low absorption when exposed to i-line, which results in a very large exposure amount required for curing, which cannot meet the needs of efficient production.
A photosensitive organic insulating material composition containing chalcone compounds and polyvinyl cinnamate was used to achieve rapid curing by increasing absorption in the i-line range and optimizing the composition ratio and photocuring conditions.
Without increasing the exposure, the material's i-line absorption was improved, the curing time was shortened, and the production efficiency was increased, meeting the needs of high-efficiency production.
Smart Images

Figure BDA0005587045490000061 
Figure BDA0005587045490000071 
Figure BDA0005587045490000072
Abstract
Description
Technical Field
[0001] This invention relates to photosensitive organic insulating material compositions, insulating films, gate insulating films, transistors, electronic devices, and methods for manufacturing transistors. Background Technology
[0002] Organic insulating film materials used in organic electronic devices such as organic thin-film transistors (OTFTs) sometimes employ materials with photosensitive properties that can be directly patterned. For example, Non-Patent Document 1 discloses an OTFT that uses polyvinyl cinnamate (also known as poly(vinyl cinnamate), hereinafter sometimes referred to as PVCi) as a photosensitive resin material as the gate insulating film. However, when the light used for exposure is i-line (wavelength 365 nm), the absorption of i-line is very small, and if an i-line monochromatic light source is used, there is a problem that curing requires a very large exposure. In this context, there is a need for a photosensitive organic insulating composition that maintains the same level of insulating properties as PVCi, and has high i-line absorption, so that even when using an i-line monochromatic light source, curing does not require a large exposure.
[0003] Existing technical documents
[0004] Non-patent literature
[0005] Non-patent literature 1: Feng, L. et al. Unencapsulated Air-stable Organic Field Effect Transistor by All Solution Processes for Low Power Vapor Sensing. Sci. Rep. 6, 20671; doi: 10.1038 / srep20671 (2016). Summary of the Invention
[0006] The first aspect of the present invention is a photosensitive organic insulating material composition comprising chalcone compounds and polyvinyl cinnamate.
[0007] The second aspect of the present invention is an insulating film of a photocurable product of the photosensitive organic insulating material composition of the first aspect.
[0008] The third aspect of the present invention is a gate insulating film of a photocurable composition of a photosensitive organic insulating material, which is the first aspect.
[0009] The fourth aspect of the present invention is a transistor having the gate insulating film of the third aspect.
[0010] The fifth aspect of the present invention is an electronic device having a thin-film transistor of the fourth aspect.
[0011] The sixth aspect of the present invention is a method for manufacturing a gate insulating film, which includes: a step of coating a photosensitive organic insulating material composition of the first aspect onto a substrate; and a step of curing the aforementioned photosensitive organic insulating material composition by exposure to form a gate insulating film.
[0012] The seventh aspect of the present invention is a method for manufacturing a transistor, which includes a step of forming a gate insulating film using the gate insulating film manufacturing method of the sixth aspect. Attached Figure Description
[0013] [ Figure 1 [Figure showing the cross-sectional shapes of organic thin-film transistors. (a): Bottom-gate-top-contact organic thin-film transistor; (b): Bottom-gate-bottom-contact organic thin-film transistor; (c): Top-gate-top-contact organic thin-film transistor; (d): Top-gate-bottom-contact organic thin-film transistor.]
[0014] [ Figure 2 This is a schematic cross-sectional view showing the structure of the bottom-gate-bottom-contact organic thin-film transistor as Example 1.
[0015] [ Figure 3 [ ] is a schematic diagram of a metal-insulator-metal structure prepared for studying the electrical properties of an organic insulating film obtained from the composition prepared in Example 1.
[0016] [ Figure 4 [Graph showing the residual film rate of the insulating films obtained in Examples 1, 6, and Comparative Example 1 relative to the exposure amount.]
[0017] [ Figure 5 This is a graph showing the residual film rate of the insulating films obtained in Examples 1, 6, and Comparative Example 1, relative to the exposure amount. Figure 4 Enlarged image.
[0018] [ Figure 6 [To illustrate Examples 1, 6, and Comparative Example 1] Figure 3 The diagram shows the leakage current between the upper and lower electrodes of the MIM structure.
[0019] [ Figure 7 [A diagram illustrating the fabrication method of the organic thin-film transistor in Examples 1 and 16.]
[0020] [ Figure 8 [Image showing a microscope image of the OTFT completed in Example 1.]
[0021] [ Figure 9 This is a graph showing the transmission characteristics of the fabricated OTFT and the results of the bias stress test.
[0022] [ Figure 10 To illustrate the V of the fabricated OTFT TH A graph showing the results of the offset.
[0023] [ Figure 11 [A graph showing the residual film rate of the insulating film obtained in Example 16 relative to the exposure amount.]
[0024] [ Figure 12 This is a graph showing the residual film percentage of the insulating film obtained in Example 16 relative to the exposure amount. Figure 11 Enlarged image.
[0025] [ Figure 13 [To illustrate Example 16 and Comparative Example 1] Figure 3 The diagram shows the leakage current between the upper and lower electrodes of the MIM structure.
[0026] [ Figure 14 [Image showing a microscope image of the OTFT completed in Example 16.]
[0027] [ Figure 15 The transmission characteristics and bias stress test results of the OTFT fabricated in Example 16 are shown.
[0028] [ Figure 16 The transmission characteristics and bias stress test results of the OTFT fabricated in Comparative Example 1 are shown. Detailed Implementation
[0029] (Photosensitive organic insulating material composition)
[0030] Hereinafter, the photosensitive organic insulating material composition of the present invention will be described in detail using the first embodiment and the second embodiment.
[0031] [First Implementation]
[0032] The photosensitive organic insulating material composition of the first embodiment contains chalcone compounds and polyvinyl cinnamate (PVCi).
[0033] Chalcones
[0034] Chalcone compounds are chalcone derivatives such as (unsubstituted) chalcones and substituted chalcones. Examples of substituted chalcones include, for instance, chalcones having one or more substituents selected from the group consisting of alkyl groups having 1 to 5 carbon atoms, alkoxy groups having 1 to 5 carbon atoms, polyoxyalkyl groups having 1 to 5 carbon atoms, alkylamino groups having 1 to 5 carbon atoms, thioalkyl groups having 1 to 5 carbon atoms, sulfonyl groups, nitro groups, cyano groups, etc. Preferably, chalcones have one or more substituents selected from the group consisting of alkyl groups having 1 to 5 carbon atoms, alkoxy groups having 1 to 5 carbon atoms, polyoxyalkyl groups having 1 to 5 carbon atoms, etc. The number of substituents is preferably 1 to 3, more preferably 1. The substitution position is preferably located on the benzene ring on the olefin side of the unsaturated carbonyl group, more preferably at the ortho or para position. From the viewpoint of facilitating photodimerization and increasing i-line absorption, it is preferable to use a chalcone in which an alkoxy group having 1 to 5 carbon atoms is substituted at the para position of the benzene ring on the olefin side of the unsaturated carbonyl group, and more preferably an alkoxy group having 1 to 3 carbon atoms.
[0035] Specific examples of chalcone compounds include, for example, chalcone, methoxychalcone, etc. More preferably, chalcone, 2-methoxychalcone, and 4-methoxychalcone. 4-methoxychalcone (hereinafter sometimes simply referred to as methoxychalcone) is even more preferred.
[0036] The chalcone compounds involved in this embodiment can be used alone or in combination of two or more.
[0037] Polyvinyl cinnamate (PVCi)
[0038] Polyvinyl cinnamate is also known as poly(vinyl cinnamate). For example, it can be obtained from Sigma-Aldrich Japan Co., Ltd.
[0039] Solvent
[0040] The photosensitive organic insulating material composition of this embodiment may further include a solvent. Examples of solvents include alcohol-based solvents, ester-based solvents, hydrocarbon-based aromatic solvents, amide-based solvents, ketone-based solvents, glycol ether-based solvents, and ether-based solvents. From the viewpoint of solubility and film-forming properties, ester-based and ketone-based solvents are preferred, among which propylene glycol 1-monomethyl ether 2-acetate (PGMEA) and cyclopentanone are preferred.
[0041] <Other Ingredients>
[0042] To improve weather resistance and lightfastness, known antioxidants, light stabilizers, and UV absorbers can be added. To improve adhesion, known adhesion promoters can be added. To improve leveling, surface wettability, or hydrophobicity, known surface modifiers can be added.
[0043] <Composition ratio of the composition>
[0044] The photosensitive organic insulating material composition of this embodiment may contain the above-mentioned chalcone compounds and polyvinyl cinnamate in the following mass ratio. The total mass ratio of the chalcone compounds to the polyvinyl cinnamate is 0.01 to 1, preferably 0.01 to 0.3, more preferably 0.03 to 0.3, and even more preferably 0.05 to 0.1.
[0045] In the photosensitive organic insulating material composition of this embodiment, the total amount of chalcone compounds and polyvinyl cinnamate is preferably 10% to 30% by mass, more preferably 10% to 15% by mass, relative to 100% by mass of the total composition.
[0046] In the photosensitive organic insulating material composition of this embodiment, the total amount of chalcone compounds is preferably 0.1% to 15% by mass, more preferably 0.1% to 3% by mass, relative to 100% by mass of the total composition.
[0047] <i-line sensitivity of the composition>
[0048] The photosensitive organic insulating material composition of this embodiment preferably has an absorption spectral peak in the wavelength range of 300–370 nm, more preferably in the wavelength range of 320–370 nm, even more preferably in the wavelength range of 340–370 nm, and most preferably has an absorption spectral peak at the i-line (365 nm). In addition to polyvinyl cinnamate, the photosensitive organic insulating material composition of this embodiment also contains chalcone compounds, therefore, compared to the case containing only polyvinyl cinnamate, the absorption at the i-line is increased. As a result, when using an i-line exposure machine with the same light intensity, the time required for photocuring is shortened. This significantly improves productivity.
[0049] The light absorption intensity at the i-line of the photosensitive organic insulating material composition of this embodiment can be adjusted by the type and content of the chalcone compound. For example, when the chalcone compound is an unsubstituted chalcone, the chalcone compound is preferably 10% to 50% by mass of 100% by mass of the components (solid components) excluding the solvent in the photosensitive organic insulating material composition. Furthermore, when the chalcone compound is a methoxychalcone, the chalcone compound is preferably 5% to 25% by mass.
[0050] [Second Implementation]
[0051] The photosensitive organic insulating material composition of the second embodiment comprises a polymer having a chalcone backbone.
[0052] Polymers with a chalcone backbone
[0053] The chalcone backbone of the polymer described in this embodiment refers to the structure of various chalcone compounds contained in the photosensitive organic insulating material composition of the first embodiment described above. The chalcone compounds described in this embodiment have the same meaning as those described in the first embodiment, and their preferred examples are also the same. The chalcone backbone of the polymer described in this embodiment is preferably a structure contained in the side chains connected to the main chain of the polymer.
[0054] The main chain of the aforementioned polymer involved in this embodiment is preferably a vinyl polymer chain generated by the polymerization reaction of monomers having olefinic unsaturated bonds.
[0055] The polymer with a chalcone backbone involved in this embodiment preferably has a vinyl polymer backbone and side chains containing a chalcone backbone.
[0056] The polymer with a chalcone backbone involved in this embodiment may include side chains without a chalcone backbone, in addition to a vinyl polymer backbone and side chains containing a chalcone backbone. Preferably, the polymer with a chalcone backbone involved in this embodiment does not contain any other side chains besides a vinyl polymer backbone and side chains containing a chalcone backbone.
[0057] The polymer with a chalcone skeleton involved in this embodiment is preferably a polymer or copolymer containing a monomer of a substituted chalcone compound having an olefinically unsaturated group. The aforementioned substituted chalcone compound having an olefinically unsaturated group is preferably at least one selected from the group consisting of chalcones having an olefinically unsaturated group and chalcones having an olefinically unsaturated group and a methoxy group.
[0058] As a specific example of a polymer having a chalcone skeleton involved in this embodiment, polymers represented by the following formulas (1) to (3) can be cited.
[0059] [Chemical Formula 1]
[0060]
[0061] (In equation (1), n1 is an integer from 1 to 1000.)
[0062] [Chemical Formula 2]
[0063]
[0064] (In equation (2), n2 is an integer from 1 to 1000.)
[0065] [Chemical Formula 3]
[0066]
[0067] (In equation (3), n3 is an integer from 1 to 1000.)
[0068] The weight-average molecular weight of the polymer with a chalcone backbone involved in this embodiment is preferably 5,000 to 100,000, more preferably 10,000 to 80,000, and even more preferably 20,000 to 50,000.
[0069] The weight-average molecular weight can be determined using gel permeation chromatography (GPC).
[0070] In the polymer having a chalcone skeleton according to this embodiment, the content of the chalcone skeleton (from the structure of chalcone compounds, for example, the structure of compound 3 of the following route other than the -OH group) is preferably 20% to 97% by mass, more preferably 50% to 80% by mass, relative to 100% by mass of the polymer.
[0071] <Method for manufacturing polymers with a chalcone backbone>
[0072] The method for manufacturing polymers with a chalcone backbone involved in this embodiment uses the polymer of formula (2) above as an example, and will be described in detail below.
[0073] The polymer manufacturing method involved in this embodiment includes: a step of synthesizing an olefinic unsaturated compound having a chalcone backbone; and a polymerization step of polymerizing the aforementioned olefinic unsaturated compound to form a vinyl polymer backbone.
[0074] The aforementioned alkene-bonded unsaturated compounds with a chalcone skeleton can be prepared using known methods that react a compound having a hydroxyl group and a chalcone skeleton with an acyl chloride having an alkene-bonded unsaturated group in a solvent. For example, compound 3 is synthesized using the method described in Non-Patent Literature 2, as shown in Route 1 below. A method for synthesizing compound 5 is given by reacting compound 3, the resulting phenolic derivative (or, using Biosynth to prepare 4'-hydroxy-4-methoxychalcone), with compound 4.
[0075] [Chemical Formula 4]
[0076]
[0077] (Non-patent document 2: X. Yang et al., Synthesis of a series of noveldihydroartemisinin derivatives containing a substituted chalcone with greater cytotoxic effects in leukemia cells, Bioorganic & Medicinal Chemistry Letters, Volume 19, Issue 15, (2009), Pages 4385-4388.)
[0078] In the polymerization process of polymerizing olefinic unsaturated compounds, for example, when olefinic unsaturated compounds are subjected to free radical copolymerization, the free radical copolymerization can be carried out using known methods such as solution polymerization, emulsion polymerization, suspension polymerization and bulk polymerization.
[0079] The solvent used in solution polymerization is not limited as long as it can dissolve the monomers described above and the polymer of the present invention. Examples include toluene, xylene, diethyl ether, tetrahydrofuran, 1,4-dioxane, dimethylformamide, dimethyl sulfoxide, etc. These solvents can also be mixed and used.
[0080] The polymerization temperature is selected based on the initiator used, but there are no particular limitations. There are no particular limitations on the initiator; examples include azo initiators such as azobisisobutyronitrile (AIBN), and peroxide initiators such as benzoyl peroxide and di-tert-butyl peroxide. As a specific example, 2,2'-azobisisobutyronitrile (AIBN) can be cited. There are no limitations on the reaction time, which can be set according to the half-life of the initiator used, but from an economic point of view, 4 to 30 hours is preferred.
[0081] For example, as shown in route 2 below, compound 5 obtained above is polymerized to synthesize compound 6.
[0082] The conditions for the synthesis reaction are described in detail in the examples. Additionally, the evaluation results for compound 6 are also described in the examples.
[0083] [Chemical Formula 5]
[0084]
[0085] In the above-described polymerization process, the olefinic unsaturated monomers used as raw materials for the polymerization reaction may include, in addition to olefinic unsaturated compounds with a chalcone skeleton such as compound 5 from route 2, olefinic unsaturated compounds without a chalcone skeleton. When olefinic unsaturated compounds without a chalcone skeleton are included, the resulting polymer has side chains that include both chalcone skeleton side chains and side chains without a chalcone skeleton. In this case, the total mass of olefinic unsaturated compounds without a chalcone skeleton is preferably 0 to 50 parts by mass, more preferably 0 to 30 parts by mass, and even more preferably 0 parts by mass, relative to 100 parts by mass of the total mass of the olefinic unsaturated compounds with a chalcone skeleton.
[0086] Solvent
[0087] The photosensitive organic insulating material composition of this embodiment may further include a solvent. Examples of solvents include alcohol-based, ester-based, and ketone-based solvents. Among these, propylene glycol 1-monomethyl ether 2-acetate (PGMEA) and cyclopentanone are preferred. Alternatively, the solvent used in the above polymerization reaction can be used directly as part of the solvent of the composition.
[0088] <Other Ingredients>
[0089] To improve weather resistance and lightfastness, known antioxidants, light stabilizers, and UV absorbers can be added. To improve adhesion, known adhesion promoters can be added. To improve leveling, surface wettability, or hydrophobicity, known surface modifiers can be added.
[0090] <Composition ratio of the composition>
[0091] In the photosensitive organic insulating material composition of this embodiment, of the components (solid components) excluding the solvent, the polymer having the chalcone backbone is preferably 50% to 100% by mass, more preferably 75% to 100% by mass. It is further preferably 100% by mass. Chalcone compounds and polyvinyl cinnamate may be included in the following mass ratio.
[0092] In the photosensitive organic insulating material composition of this embodiment, the total amount of the polymer having the chalcone backbone is preferably 10% to 30% by mass, more preferably 10% to 15% by mass, relative to 100% by mass of the total composition.
[0093] <i-line sensitivity of the composition>
[0094] The photosensitive organic insulating material composition of this embodiment preferably has an absorption spectral peak in the wavelength range of 300–370 nm, more preferably in the wavelength range of 320–370 nm, even more preferably in the wavelength range of 340–370 nm, and most preferably has an absorption spectral peak at the i-line (365 nm). The photosensitive organic insulating material composition of this embodiment contains a polymer with a chalcone backbone, therefore, compared to the prior art which only contains polyvinyl cinnamate, the absorption at the i-line is increased. As a result, the time required for photocuring is shortened when using an i-line exposure machine with the same light intensity. This significantly improves productivity.
[0095] The light absorption intensity at the i-line of the photosensitive organic insulating material composition of this embodiment can be adjusted by the type of chalcone compound relative to the chalcone backbone, the content of the chalcone backbone in the polymer, etc. For example, when the chalcone compound is methoxychalcone, that is, when a polymer with a methoxychalcone backbone is present, 50 to 90 parts by mass are preferred. When the absorption at the i-line is high, the deep curing property decreases, resulting in reduced photocuring in thick films or reduced end-drawing properties. In order to obtain excellent photocurability with the desired film thickness, the content can be adjusted arbitrarily.
[0096] (Organic insulating film)
[0097] The organic insulating film of one embodiment of the present invention (hereinafter referred to as the organic insulating film of this embodiment) is a film (photocured product) obtained by forming one or more photosensitive organic insulating material compositions selected from the group consisting of the first and second embodiments described above (hereinafter sometimes referred to as the compositions involved in this embodiment) on a substrate and then photocuring them. The compositions involved in this embodiment can be printed on various substrates. As for the organic solvent used, any solvent that dissolves the compounds contained in the composition without dissolving the organic semiconductor materials used in the manufacture of devices such as organic thin-film transistors can be used without any restrictions. Examples include: aromatic hydrocarbon solvents such as cyclohexane, benzene, toluene, xylene, ethylbenzene, isopropylbenzene, N-hexylbenzene, tetrahydronaphthalene, decahydronaphthalene, isopropylbenzene, and chlorobenzene; chlorinated aliphatic hydrocarbon compounds such as dichloromethane and 1,1,2-trichloroethylene; aliphatic cyclic ether compounds such as tetrahydrofuran, tetrahydropyran, and dioxane; ketone compounds such as methyl ethyl ketone, cyclopentanone, and cyclohexanone; ester compounds such as ethyl acetate, dimethyl phthalate, methyl salicylate, amyl acetate, and propylene glycol 1-monomethyl ether 2-acetate (PGMEA); alcohols such as n-butanol, ethanol, and isobutanol; and solvents such as 1-nitropropane, carbon disulfide, and limonene. These solvents can be mixed and used as needed. Preferably, the organic solvent is the same as the organic solvent used in the above synthesis, and more preferably, propylene glycol 1-monomethyl ether 2-acetic acid ester (PGMEA), cyclopentanone, etc.
[0098] There are no restrictions on the coating or printing method. For example, spinning, dripping, dip coating, doctor blade coating, pad printing, squeegee coating, roller coating, rod bar coating, air knife coating, wire rod coating, flow coating, gravure printing, flexographic printing, screen printing, inkjet printing, letterpress reversal printing, etc. can be used for printing.
[0099] The composition according to this embodiment includes a photocrosslinking group with photodimerization reactivity. Radiation is preferably used in this photocrosslinking process; examples of radiation include ultraviolet and visible light with wavelengths of 245–450 nm. From the viewpoint of maximizing the effects of the present invention, radiation near the i-line is preferred, and more preferably an i-line monochromatic light source. The radiation dose can be appropriately varied depending on the composition of the polymer; for example, 100–300 mJ / cm³ is possible. 2 To prevent a decrease in crosslinking degree and to improve economic efficiency by shortening the process time, a value of 50–200 mJ / cm is preferred. 2There are no particular restrictions on the environment for irradiation with ultraviolet or visible light; it can be carried out in the atmosphere, in an inert gas, or under a certain amount of inert gas flow. A photosensitizer can also be added to the composition as needed to promote the photocrosslinking reaction. There are no restrictions on the photosensitizer used; for example, benzophenone compounds, anthraquinone compounds, thioxanthone compounds, and nitrophenyl compounds can be mentioned. Furthermore, two or more photosensitizers can be used in combination as needed. From the viewpoint of improving the electrical properties of the organic insulating film of this embodiment, it is preferable that it does not substantially contain a photosensitizer. Here, a photosensitizer refers to a substance that, by absorbing light, transfers the energy it gains to other substances, thereby contributing to the photocrosslinking reaction. Examples include benzophenone compounds, anthraquinone compounds, thioxanthone compounds, and nitrophenyl compounds. The chalcone compounds included in the photosensitive organic insulating material composition of the first embodiment described above are substances that absorb light and participate in the photocrosslinking reaction themselves, and are not photosensitizers.
[0100] "Substantially does not contain" means that it contains only a small amount to the extent that no photosensitivity effect is observed. For example, in the composition involved in this embodiment, it is preferably in the range of 0% to 0.05% by mass, more preferably in the range of 0% to 0.01% by mass, even more preferably in the range of 0% to 0.05% by mass, and even more preferably 0% by mass.
[0101] Furthermore, the photosensitive organic insulating material composition used in the organic insulating film of this embodiment can efficiently perform photocrosslinking in a short time. To achieve efficient photocrosslinking in an even shorter time, for example, when using an i-line, it is preferable to keep the light irradiation time to within 2 minutes. It should be noted that, from the perspective of suitable control of the crosslinking time, for example, when using an i-line, it is further preferable to keep the light irradiation time to within 1 minute.
[0102] The organic insulating film of this embodiment can be suitably used as an insulating film for various devices such as organic thin-film transistors. The organic insulating film of this embodiment is particularly suitable for use as a gate insulating film for organic thin-film transistors, as described later.
[0103] (Organic thin-film transistor)
[0104] The organic thin-film transistor of this embodiment can be Figure 1Any of the following element structures are shown: bottom-gate-top contact (A), bottom-gate-bottom contact (B), top-gate-top contact (C), and top-gate-bottom contact (D). The polymer of this embodiment is particularly applicable to elements in forms (A) and (B). In this embodiment, an element in form (B) is used. Here, 1 represents the organic semiconductor layer, 2 represents the substrate, 3 represents the gate electrode, 4 represents the gate insulating layer, 5 represents the source electrode, and 6 represents the drain electrode.
[0105] In this organic thin-film transistor, there are no particular limitations on the substrate that can be used, as long as it ensures sufficient flatness for fabricating the device. Examples include inorganic substrates such as glass, quartz, alumina, highly doped silicon, tantalum dioxide, tantalum pentoxide, and indium tin oxide; plastics; metals such as gold, copper, chromium, titanium, and aluminum; ceramics; coated paper; and surface-coated nonwoven fabrics. Composite materials containing these materials or materials obtained by multilayering these materials can also be used. In addition, the surfaces of these materials can be coated to adjust the surface tension.
[0106] Examples of plastics used as substrates include polyethylene terephthalate, polyethylene naphthalate, triacetyl cellulose, polycarbonate, polymethyl acrylate, polymethyl methacrylate, polyvinyl chloride, polyethylene, ethylene-vinyl acetate copolymer, polymethylpentene-1, polypropylene, cyclic polyolefins, fluorinated cyclic polyolefins, polystyrene, polyimide, polyvinylphenol, polyvinyl alcohol, poly(diisopropyl fumarate), poly(diethyl fumarate), poly(diisopropyl maleate), polyethersulfone, polyphenylene sulfide, polyphenylene ether, polyester elastomers, polyurethane elastomers, polyolefin elastomers, polyamide elastomers, and styrene block copolymers. Furthermore, two or more of the above-mentioned plastics can be laminated together as a substrate.
[0107] Examples of conductive materials that can be used as the gate electrode, source electrode, or drain electrode in this embodiment include gold, silver, aluminum, copper, titanium, platinum, chromium, polysilicon, silicide, indium tin oxide (ITO), and tin oxide. Alternatively, these conductive materials can be stacked in multiple layers.
[0108] Furthermore, in bottom-gate-top contact (A) type devices and bottom-gate-bottom contact (B) type devices, electrodes are formed on the aforementioned organic semiconductor layer or on the aforementioned gate insulating film. In this case, there are no particular limitations on the method of forming the electrodes, and examples include vapor deposition, high-frequency sputtering, electron beam sputtering, etc. Ink made by dissolving nanoparticles of the aforementioned conductive material in water or organic solvents can also be used, employing methods such as solution spin coating, drop coating, dip coating, doctor blade coating, mold coating, pad printing, roll coating, gravure printing, flexographic printing, screen printing, inkjet printing, and letterpress reverse printing. In addition, if necessary, treatment can be performed to adsorb fluoroalkyl mercaptan, fluoroallyl mercaptan, etc., onto the electrodes.
[0109] There are no limitations on the organic semiconductors that can be used in the organic thin-film transistor of this embodiment. Any N-type and P-type organic semiconductors can be used, or it can be used as a bipolar transistor composed of N-type and P-type semiconductors. For example, polypyrrole, polythiophene, polyaniline, polyallylamine, fluorene, polycarbazole, polyindole, poly(p-phenylacetylene), etc., can be used. In addition, low-molecular-weight substances that are soluble in organic solvents can be used, such as polycyclic aromatic derivatives such as pentanebenzene, phthalocyanine derivatives, perylene derivatives, tetrathiofulvalene derivatives, tetracyanobenzoquinone dimethane derivatives, fullerenes, carbon nanotubes, etc. Specifically, the condensate of 9,9-di-n-octylfluorene-2,7-di(ethylene borate) and 5,5'-dibromo-2,2'-bithiophene can be cited.
[0110] In this embodiment, as a method for forming the organic semiconductor layer, a method of dissolving the organic semiconductor in an organic solvent and then coating or printing can be appropriately used, but there are no limitations as long as a thin film of the organic semiconductor layer can be formed. When printing with a solution formed by dissolving the organic semiconductor layer in an organic solvent, the solution concentration varies depending on the structure of the organic semiconductor and the solvent used, but from the viewpoint of forming a more uniform semiconductor layer and reducing the layer thickness, 0.5 to 5% by weight is preferred. As for the organic solvent used at this time, there are no restrictions as long as the organic semiconductor is dissolved at a certain concentration suitable for film formation. Examples include hexane, heptane, octane, decane, dodecane, tetradecane, decahydronaphthalene, indane, 1-methylnaphthalene, 2-ethylnaphthalene, 1,4-dimethylnaphthalene, mixtures of dimethylnaphthalene isomers, toluene, xylene, ethylbenzene, 1,2,4-trimethylbenzene, mesitylene, isopropylbenzene, pentylbenzene, hexylbenzene, tetrahydronaphthalene, octylbenzene, cyclohexylbenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, trichlorobenzene, 1,2-dimethoxybenzene, 1, 3-Dimethoxybenzene, γ-Butyrolactone, 1,3-Butanediol, Ethylene glycol, Benzyl alcohol, Glycerol, Cyclohexanol acetate, 3-Methoxybutyl acetate, Ethylene glycol monomethyl ether acetate, Ethylene glycol monobutyl ether acetate, Propylene glycol monomethyl ether acetate, Anisole, Cyclohexanone, Trimethylbenzene, 3-Methoxybutyl acetate, Cyclohexanol acetate, Dipropylene glycol diacetate, Dipropylene glycol methyl ether acetate, Diethylene glycol monobutyl ether acetate, Diethylene glycol monoethyl ether acetate, 1,6-Hexanediol diacetate, 1,3-Butanediol diacetate, 1,4-Butanediol diacetate Ethyl acetate, phenyl acetate, dipropylene glycol dimethyl ether, dipropylene glycol methyl-N-propyl ether, tetradehydrophenanthrene, 1,2,3,4,5,6,7,8-octahydrophenanthrene, decahydro-2-naphthol, 1,2,3,4-tetrahydro-1-naphthol, α-terpineol, isophorone triacetate, decahydro-2-naphthol, dipropylene glycol dimethyl ether, 2,6-dimethyl anisole, 1,2-dimethyl anisole, 2,3-dimethyl anisole, 3,4-dimethyl anisole, 1-benzothiophene, 3-methylbenzothiophene, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane Species such as chloroform, dichloromethane, tetrahydrofuran, 1,2-dimethoxyethane, dioxane, cyclohexanone, acetone, methyl ethyl ketone, diethyl ketone, diisopropyl ketone, acetophenone, N,N-dimethylformamide, N-methyl-2-pyrrolidone, and limonene are suitable. However, to obtain a crystalline film with preferred properties, solvents with high solubility for organic semiconductors and boiling points above 100°C are appropriate. Xylene, isopropylbenzene, anisole, cyclohexanone, mesitylene, 1,2-dichlorobenzene, 3,4-dimethyl anisole, pentylbenzene, tetrahydronaphthalene, cyclohexylbenzene, and decahydro-2-naphthol are also preferred. Alternatively, a mixed solvent prepared by mixing two or more of the aforementioned solvents in appropriate proportions can also be used.
[0111] Depending on the requirements, various organic and inorganic polymers or oligomers, or organic and inorganic nanoparticles, can be added to the organic semiconductor layer in solid form or in the form of a dispersion of nanoparticles in water or an organic solvent. A polymer solution can be coated onto the aforementioned polymer dielectric layer to form a protective film. Furthermore, various moisture-proof coatings, light-resistant coatings, etc., can be applied to this protective film as needed.
[0112] Examples of conductive materials that can be used as gate, source, or drain electrodes in the organic thin-film transistor of this embodiment include inorganic electrodes such as aluminum, gold, silver, copper, highly doped silicon, polycrystalline silicon, silicides, tin oxides, indium oxide, indium tin oxide, chromium, platinum, titanium, tantalum, graphene, and carbon nanotubes, or organic electrodes such as doped conductive polymers (e.g., PEDOT-PSS). These conductive materials can also be stacked in multiple layers. Furthermore, to improve carrier injection efficiency, these electrodes can be surface-treated using a surface treatment agent. Examples of such surface treatment agents include thiophenol and pentafluorothiophenol.
[0113] Furthermore, there are no particular limitations on the methods for forming electrodes on the aforementioned substrate, insulating layer, or organic semiconductor layer. Examples include vapor deposition, high-frequency sputtering, and electron beam sputtering. Inks made by dissolving nanoparticles of the aforementioned conductive material in water or organic solvents can also be used, employing methods such as solution spin coating, drop coating, dip coating, doctor blade coating, mold coating, pad printing, roller coating, gravure printing, flexographic printing, screen printing, inkjet printing, and letterpress reverse printing.
[0114] The organic thin-film transistor of this embodiment can, for example, be a device with a bottom-gate-bottom contact type as used in the embodiments. Figure 2 This is a schematic cross-sectional view showing the structure of a bottom-gate-bottom-contact organic thin-film transistor as an example of this embodiment. The organic thin-film transistor includes: a substrate 2; a gate electrode 3 formed on the substrate 2; a gate insulating layer 4 formed on the gate electrode 3; a source electrode 5 and a drain electrode 6 formed on the gate insulating layer 4 with a channel portion sandwiched between them; and an organic semiconductor layer 1 formed on the electrode.
[0115] From the viewpoint of the practicality of organic thin-film transistor devices, the mobility of the organic thin-film transistor in this embodiment is preferably 0.20 cm⁻¹. 2 / Vs and above.
[0116] From the viewpoint of the practicality of organic thin-film transistor devices, the threshold voltage of the organic thin-film transistor in this embodiment is preferably -10.0V or higher and less than 0V.
[0117] From the viewpoint of the practicality of organic thin-film transistor devices, the leakage current density of the organic thin-film transistor in this embodiment is preferably 10. -9 A / cm 2 the following.
[0118] (Electronic devices containing organic thin-film transistors)
[0119] The electronic device of this embodiment includes the organic thin-film transistor described in this embodiment. Examples of electronic devices according to this embodiment include organic electroluminescent elements, organic photoelectric conversion elements, and displays.
[0120] Example
[0121] The present invention will be described below through examples, but the present invention is not limited to the examples.
[0122] The raw materials, apparatus, etc. used in the embodiments of the present invention will be described below.
[0123] (raw material)
[0124] Chalcone: Tokyo Chemical Industry Co., Ltd., Product Code C0071, Purity (Test Method): >98.0% (GC)
[0125] Methoxychalcone: Tokyo Chemical Industry Co., Ltd., Product Code M1409, Purity (Test Method): >98.0% (GC)
[0126] Polyvinyl cinnamate (PVCi): Sigma-Aldrich, product code 182648; Cyclopentanone: Fujifilm and Wako Pure Chemical Industries, Ltd., product code 039-09716; Purity (test method): >95.0% (GC).
[0127] PGMEA: Tokyo Chemical Industry Co., Ltd., Product Code P1171, Purity (Test Method): >98.0% (GC)
[0128] Silicon wafer: Xiangnan Electronic Materials Research Institute, P-type resistivity below 1Ωcm
[0129] Glass substrate: Shonan Electronic Materials Research Institute, soda-lime glass.
[0130] Organic semiconductor layer raw material: 2-decyl-7-phenyl[1]benzothiophene[3,2-b][1]benzothiophene, Tokyo Chemical Industry Co., Ltd., product code D5491, purity (test method): >99.5% (HPLC)
[0131] Organic semiconductor layer additive: Polystyrene, Sigma-Aldrich, product code 182427, average Mw ~280,000 (GPC)
[0132] (device)
[0133] Device for film formation: Spin coater (manufactured by Mikasa Co., Ltd., MS-A150)
[0134] i-line exposure machine: Multi-light (manufactured by Ushio Inc.)
[0135] Photolithography
[0136] Weight-average molecular weight: GPC (TOSO specification: GPC-8020)
[0137] Residual film rate: Stylus profilometer (KLA-Tencor, P16)
[0138] Evaluation of various electrical characteristics: Semiconductor parameter analyzer (Keithley Instruments: 4200A-SCS model)
[0139] (Evaluation Method)
[0140] Average molecular weight: calculated using GPC (TOSO standard: GPC-8020).
[0141] Chalcone skeleton content: calculated based on the charge ratio of the synthetic raw materials.
[0142] Residual film rate: The ratio of the film thickness after exposure and development to the film thickness before exposure.
[0143] Leakage current: obtained by current-voltage (IV) measurement of a metal-insulator-metal structure based on a semiconductor parameter analyzer.
[0144] Dielectric constant: Calculated based on capacitance measurements of metal-insulator-metal structures using a semiconductor parameter analyzer.
[0145] Transmission characteristics: obtained through a semiconductor parameter analyzer
[0146] The threshold voltage offset based on bias stress testing is obtained by applying a negative bias stress (NBS) test with a certain voltage (VGS = -20V) between the source and gate. The application time is set to 1 second, 10 seconds, 100 seconds, and 1000 seconds. After each application time, the transmission characteristics are measured, and the difference in threshold voltage is calculated.
[0147] (Synthesis example 1)
[0148] Synthesis of compounds with hydroxyl and methoxychalcone skeletons (compound 3 of route 1 above)
[0149] Compound 3: <Substance name: 4'-hydroxy-4-methoxychalcone>
[0150] Under argon atmosphere, 390 g of 4-hydroxyacetophenone (manufactured by Fujifilm and Kohden Chemical Co., Ltd.), 390 g of p-methoxybenzaldehyde (manufactured by Fujifilm and Kohden Chemical Co., Ltd.), and 5.5 L of methanol (manufactured by Fujifilm and Kohden Chemical Co., Ltd.) were mixed in a 20 L four-necked flask. Then, the mixture was kept in an ice bath at an internal temperature below 15 °C, and 2.7 L of 50% NaOH aqueous solution was added dropwise over 60 minutes. The ice bath was then removed, and the mixture was stirred at room temperature for 95 hours. 5.4 L of distilled water was added to a 90 L container, and the reaction mixture was then injected. Next, approximately 35 L of 1 N HCl aqueous solution was gradually added. When the internal temperature was about to exceed 30 °C, ice was added to maintain the temperature at approximately 25 °C. The pH was adjusted to approximately 4, and the precipitated solid was separated by vacuum filtration. The solid was washed with a 2 / 1, 3 L mixture of methanol and distilled water. The resulting solid was dried under reduced pressure at 50 °C for 24 hours, yielding 544.6 g of a pale yellow solid. Recrystallization with ethanol yielded 520.8 g of the target substance (71% yield).
[0151] The following shows the 1H-NMR determination results of 4'-hydroxy-4-methoxychalcone.
[0152] 1H-NMR (CDCl3) 3.86 (3H, s), 5.52 (1H, s), 6.93 (4H, m), 7.41 (1H, m), 7.60 (2H, m), 7.81 (1H, m), 8.01 (2H, m)
[0153] (Synthesis example 2)
[0154] Synthesis of olefinic unsaturated compounds with a methoxychalcone skeleton (compound 5 from route 1 above)
[0155] Compound 5: <Substance Name: (E)-4-(3-(4-methoxyphenyl)acryloyl)phenyl methacrylate>
[0156] Under argon atmosphere, 30.0 g of 4'-hydroxy-4-methoxychalcone and THF (dried) were added to a 2 L four-necked flask and dissolved. Triethylamine (15.5 g, manufactured by Fujifilm and Kohden Chemical Co., Ltd.) was added, and the mixture was cooled with ice water. Methacrylamide (14.8 g, manufactured by Fujifilm and Kohden Chemical Co., Ltd.) was added dropwise, and the mixture was stirred overnight. Water (600 mL) was added to the reactor, and the mixture was transferred to a separatory funnel for extraction with ethyl acetate (1.2 L, manufactured by Fujifilm and Kohden Chemical Co., Ltd.). The ethyl acetate layer was then washed twice with 600 mL of 5% sodium bicarbonate aqueous solution, three times with 600 mL of water, and dried with anhydrous sodium sulfate. After removing the drying agent, the mixture was concentrated under reduced pressure (40 °C / 20 mmHg) to obtain a pale yellow solid. Ethanol (600 mL) was added to the crude product, and the mixture was stirred and suspended for 30 minutes. The mixture was then filtered to obtain a white solid. The solid was dried under reduced pressure (40 °C / <1 mmHg) to obtain 30.1 g (79.2%) of the target compound.
[0157] The following shows the 1H-NMR determination results of (E)-4-(3-(4-methoxyphenyl)acryloyl)phenyl methacrylate.
[0158] 1H-NMR (CDCl3) 2.09 (3H, s), 3.87 (3H, s), 5.81 (1H, m), 6.39 (1H, m), 6.93 (2H, d), 7.26 (2H, d), 7.38 (1H, m), 7.63 (2H, d), 7.78 (1H, m), 8.08 (2H, d)
[0159] (Synthesis example 3)
[0160] Synthesis of a polymer with a methoxychalcone backbone (PMC: poly(4-methoxychalcone)) (the compound represented by formula (2) above, compound 6 of route 2)
[0161] As shown in route 2 above, compound 5 obtained in synthesis example 2 is polymerized to synthesize compound 6.
[0162] Under argon atmosphere, (E)-4-(3-(4-methoxyphenyl)acryloyl)phenyl methacrylate and degassed DMF were added to a 3L four-necked flask and stirred. AIBN (3.82g, manufactured by Fujifilm and Kohden Chemical Co., Ltd.) was then added, and the mixture was heated to 60°C and stirred for 21 hours. After cooling, the mixture was added dropwise to 30L of methanol. After stirring for 60 minutes, the mixture was filtered under reduced pressure, washed three times with 2L of methanol, and the resulting solid was dried under reduced pressure (50°C / <1mmHg) to obtain 135g of the target PMC.
[0163] The following shows the 1H-NMR determination results of PMC.
[0164] 1H-NMR (CDCl3) 1.57 (3H, br), 1.94 (1H, br), 3.75 (3H, br), 6.83 (2H, br), 7.31 (6H, m, br), 7.96 (2H, br)
[0165] The weight-average molecular weight, chalcone skeleton content, and solid composition of compound 6 were evaluated, and the results are shown below. The evaluation method is described above.
[0166] Weight-average molecular weight: 44131
[0167] Chalcone skeleton content: 74 parts by weight
[0168] (Example 1)
[0169] [Preparation of the composition]
[0170] The composition of this embodiment was prepared by dissolving 3% by mass of chalcone and 10% by mass of polyvinyl cinnamate in cyclopentanone.
[0171] [Preparation and Evaluation of Organic Insulating Films]
[0172] Figure 3 This is a schematic diagram of a metal-insulator-metal structure prepared to study the electrical properties of the organic insulating film obtained from the composition prepared in this embodiment. Using the composition prepared in this embodiment, a film was formed on a silicon wafer by spin coating at 2000 rpm for 60 seconds. The film thickness before photolithography was 450 nm. The film was pre-baked at 80°C for 20 minutes, exposed to various i-line exposures, and developed using PGMEA. Figure 4 and Figure 5 ( Figure 4 (The magnified image) shows the residual film percentage relative to the exposure amount. For example... Figure 5 As shown, at 2400mJ / cm 2 Under these conditions, the residual film rate reaches approximately 1%.
[0173] Figure 6 for Figure 3 The leakage current between the upper and lower electrodes of the MIM structure shown.
[0174] according to Figure 6 It can be seen that the organic insulating film of Example 1 has substantially the same insulating properties as the organic insulating film of Comparative Example 1 described later.
[0175] In addition, the dielectric constant of the organic insulating film of Example 1 was also evaluated.
[0176] The evaluation results of the organic insulating film of Example 1 are shown in Table 1.
[0177] [Fabrication and Evaluation of Organic Thin Film Transistors]
[0178] Figure 7 This is a method for fabricating organic thin-film transistors based on this embodiment. Additionally, Figure 2 This is a schematic diagram of the stacked structure of the fabricated organic thin-film transistor.
[0179] First of all, Figure 7 In step (1), the gate electrode is formed. An aluminum (Al) film of 50 nm is deposited on a soda-lime glass wafer, which serves as the insulating substrate, using a resistance-heated vacuum evaporation method. Next, electrode processing is performed. First, a positive photoresist, SUMIRESIST PFI-34A (manufactured by Sumitomo Chemical), is spin-coated at 1500 rpm for 45 seconds on the Al layer surface. The film is then pre-baked at 105°C for 10 minutes to remove the solvent from the photoresist film. Next, a photomask is used to apply the photoresist at 270 mJ / cm². 2 The gate electrode pattern was exposed using an i-line dose and baked (PEB) at 105°C for 10 minutes. Then, the exposed areas were immersed in tetramethylammonium hydroxide (TMAH) at 25°C for 1 minute to remove the resist. After rinsing the substrate with pure water, it was dried by blowing N2 gas and then baked at 105°C for 10 minutes. Next, the Al layer was processed. The substrate was immersed in a heated mixed acid aqueous solution (H3PO4:CH3COOH:HNO3:H2O = 10:1:1:2 by weight) to etch the exposed Al. The resist on the substrate was removed with acetone, rinsed with pure water, and then dried by blowing N2 gas.
[0180] Next, in Figure 7 In step (2), a gate insulating film is formed. The composition obtained in this example is spin-coated at 2000 rpm for 60 seconds and pre-baked at 80°C for 20 minutes. Then, a photomask is used to apply the film at 2400 mJ / cm². 2 The i-line dose is cured. Then, it is immersed in PGMEA as a developer at room temperature (25°C), with only the pad portion of the gate electrode open. Then, it is baked at 150°C for 1 hour.
[0181] Next, in Figure 7 In step (3), the source / drain electrodes are formed. A 50nm gold (Au) film is deposited on the gate insulating film (layer) using a resistance-heated vacuum evaporation method. Next, electrode processing is performed. Figure 7 The process in (1) is performed in the same way as the resist process and the etching process.
[0182] Finally, Figure 7 In step (4), the semiconductor layer is formed. After UV treatment of the substrate with source / drain electrodes, a thiol-based self-assembled monolayer (SAM) is formed on the Au electrode surface using an immersion method. Then, a semiconductor solution containing 0.5% by mass of organic semiconductor and 0.2% by mass of polystyrene is heated to 150°C and spin-coated at 1000 rpm for 30 seconds, followed by baking at 120°C for 5 minutes. Finally, the semiconductor layer is patterned by wiping the electrode pads. A microscopic image of the completed OTFT is shown below. Figure 8 .
[0183] Figure 9 The transmission characteristics and bias stress test results of the fabricated OTFT (channel length L = 50 μm, channel width W = 500 μm) are shown. The transmission characteristics were obtained under a source / drain voltage Vds = -2 V. For the bias stress test, a bias voltage Vg = -20 V was applied between the source and gate, and the characteristic changes were observed after 1 second, 10 seconds, 100 seconds, and 1000 seconds. Figure 10 The value shown is the threshold voltage offset relative to the application time. In the gate insulating film of this embodiment, a threshold voltage offset of 0.5V was confirmed under the condition of 1000 seconds of application.
[0184] (Examples 2-15)
[0185] [Preparation of the composition]
[0186] The compositions of Examples 2 to 5 were prepared using the compositions shown in Tables 1 and 2.
[0187] [Preparation and Evaluation of Organic Insulating Films]
[0188] Instead of the composition of Example 1, the compositions of Examples 2-15 were used, and organic insulating films were prepared and evaluated using the same method as in Example 1. The results are shown in Tables 1 and 2.
[0189] [Fabrication and Evaluation of Organic Thin Film Transistors]
[0190] Instead of the composition of Example 1, the compositions of Examples 2-15 were used, and organic thin-film transistors were fabricated and evaluated using the same method as in Example 1. The results are shown in Tables 1 and 2.
[0191] (Example 16)
[0192] [Preparation of the composition]
[0193] The polymerized methoxychalcone membrane obtained in Synthesis Example 3 was dissolved in cyclopentanone at 10% by mass to prepare the composition of this example.
[0194] [Preparation and Evaluation of Organic Insulating Films]
[0195] Figure 3 This is a schematic diagram of a metal-insulator-metal structure prepared to study the electrical properties of the organic insulating film obtained from the composition prepared in this embodiment. Using the composition prepared in this embodiment, a film was formed on a silicon wafer by spin coating at 2000 rpm for 60 seconds. The film thickness before photolithography was 450 nm. The film was pre-baked at 80°C for 20 minutes, exposed to various i-line exposures, and developed with cyclopentanone. Figure 11 and Figure 12 ( Figure 11 (The magnified image) shows the residual film percentage relative to the exposure amount. For example... Figure 12 As shown, at 200 mJ / cm 2 Under these conditions, the residual film rate reaches approximately 1%.
[0196] Figure 13 for Figure 3 The leakage current between the upper and lower electrodes of the MIM structure shown.
[0197] according to Figure 13 It can be seen that the organic insulating film of Example 1 has substantially the same insulating properties as the organic insulating film of Comparative Example 1 described later.
[0198] In addition, the dielectric constant of the organic insulating film of Example 16 was also evaluated.
[0199] The evaluation results of the organic insulating film of Example 16 are shown in Table 2.
[0200] [Fabrication and Evaluation of Organic Thin Film Transistors]
[0201] Figure 7 This is a method for fabricating organic thin-film transistors based on this embodiment. Additionally, Figure 2 This is a schematic diagram of the stacked structure of the fabricated organic thin-film transistor.
[0202] First of all, Figure 7 In step (1), the gate electrode is formed. An aluminum (Al) film of 50 nm is deposited on a soda-lime glass wafer, which serves as the insulating substrate, using a resistance-heated vacuum evaporation method. Next, electrode processing is performed. First, a positive photoresist, SUMIRESIST PFI-34A (manufactured by Sumitomo Chemical), is spin-coated at 1500 rpm for 45 seconds on the Al layer surface. The film is then pre-baked at 105°C for 10 minutes to remove the solvent from the photoresist film. Next, a photomask is used to apply the photoresist at 270 mJ / cm².2 The gate electrode pattern was exposed using an i-line dose and baked (PEB) at 105°C for 10 minutes. Then, the exposed areas were immersed in tetramethylammonium hydroxide (TMAH) at 25°C for 1 minute to remove the resist. After rinsing the substrate with pure water, it was dried by blowing N2 gas and then baked at 105°C for 10 minutes. Next, the Al layer was processed. The substrate was immersed in a heated mixed acid aqueous solution (H3PO4:CH3COOH:HNO3:H2O = 10:1:1:2 by weight) to etch the exposed Al. The resist on the substrate was removed with acetone, rinsed with pure water, and then dried by blowing N2 gas.
[0203] Next, in Figure 7 In step (2), a gate insulating film is formed. The composition obtained in this example is spin-coated at 2000 rpm for 60 seconds and pre-baked at 80°C for 20 minutes. Then, a photomask is used to apply the film at 2400 mJ / cm². 2 The i-line dose is cured. Then, it is immersed in cyclopentanone as a developer at room temperature (25°C), with only the pad portion of the gate electrode open. Then, it is baked at 150°C for 1 hour.
[0204] Next, in Figure 7 In step (3), the source / drain electrodes are formed. A 50nm gold (Au) film is deposited on the gate insulating film (layer) using a resistance-heated vacuum evaporation method. Next, electrode processing is performed. Figure 7 The process in (1) is performed in the same way as the resist process and the etching process.
[0205] Finally, Figure 7 In step (4), the semiconductor layer is formed. After UV treatment of the substrate with source / drain electrodes, a thiol-based self-assembled monolayer (SAM) is formed on the Au electrode surface using an immersion method. Then, a semiconductor solution containing 0.5% by mass of organic semiconductor and 0.2% by mass of polystyrene is heated to 150°C and spin-coated at 1000 rpm for 30 seconds, followed by baking at 120°C for 5 minutes. Finally, the semiconductor layer is patterned by wiping the electrode pads. A microscopic image of the completed OTFT is shown below. Figure 13 .
[0206] Figure 15The transmission characteristics and bias stress test results of the fabricated OTFT (channel length L = 50 μm, channel width W = 500 μm) are shown. The transmission characteristics were obtained under a source / drain voltage Vds = -2 V. For the bias stress test, a bias voltage Vg = -20 V was applied between the source and gate, and the characteristic changes were observed after 1 second, 10 seconds, 100 seconds, and 1000 seconds. Figure 10 The value shown is the threshold voltage offset relative to the application time. In the gate insulating film of this embodiment, a threshold voltage offset of 0.67V was confirmed under the condition of 1000 seconds of application.
[0207] (Comparative Example 1)
[0208] The composition of this comparative example was prepared by dissolving PVCi in cyclopentanone at 10% by mass.
[0209] [Preparation and Evaluation of Organic Insulating Films]
[0210] Instead of the composition of Example 1, the composition of this comparative example was used. The resulting organic insulating film was developed using PGMEA. Otherwise, the organic insulating film was prepared and evaluated using the same method as in Example 1. The results are shown in Table 1.
[0211] [Fabrication and Evaluation of Organic Thin Film Transistors]
[0212] As a comparative example 1, in the OTFT fabrication process of Example 1 above, the gate insulating film was set as PVCi. PVCi was dissolved in cyclopentanone at 10% by mass, and a film was formed under spin-coating conditions of 2000 rpm for 60 seconds, followed by pre-baking at 80°C for 20 minutes. Next, using a photomask, it was thoroughly cured using a low-pressure mercury lamp. Then, it was immersed in cyclopentanone at room temperature (25°C), with only the pad portion of the gate electrode open. Finally, it was post-baked at 150°C for 1 hour.
[0213] Figure 16 The transmission characteristics and bias stress test results of the fabricated OTFT (channel length L = 50 μm, channel width W = 500 μm) are shown. The transmission characteristics were obtained under a source / drain voltage Vds = -2 V. For the bias stress test, a bias voltage Vg = -20 V was applied between the source and gate, and the characteristic changes were observed after 1 second, 10 seconds, 100 seconds, and 1000 seconds. Figure 9 The table shows the threshold voltage offset relative to the application time. In PVCi, a threshold voltage offset of 0.74V was confirmed under a 1000-second application condition.
[0214] [Table 1]
[0215]
[0216] [Table 2]
[0217]
[0218] The symbols in the table have the following meanings.
[0219] PVCi: Polyvinyl cinnamate
[0220] CH: Chalcone
[0221] MC: Methoxychalcone
[0222] PMC: Poly(4-methoxychalcone) CPN: Cyclopentanone
[0223] PGMEA: Propylene glycol 1-monomethyl ether 2-acetate
[0224] Explanation of reference numerals in the attached figures
[0225] 1, 11: Organic semiconductor layer
[0226] 2, 12, 22: substrate
[0227] 3, 13, 33: Gate electrode
[0228] 4, 14: Gate insulating layer
[0229] 5, 15, 35: Source electrode
[0230] 6, 16, 36: Drain electrode
[0231] 22: Substrate
[0232] 23: Electrode
[0233] 24: Insulation layer
Claims
1. A photosensitive organic insulating material composition, comprising: Chalcones; and Polyvinyl cinnamate.
2. The photosensitive organic insulating material composition according to claim 1, wherein, The chalcone compound is selected from at least one of the groups consisting of chalcone and methoxychalcone.
3. The photosensitive organic insulating material composition as described in claim 1 or 2, wherein, The total mass ratio of the chalcone compounds to the mass ratio of the polyvinyl cinnamate is 0.01 to 1.
4. The photosensitive organic insulating material composition according to any one of claims 1 to 3, wherein, The total amount of the chalcone compounds and the polyvinyl cinnamate is 10% to 30% by mass relative to 100% by mass of the total amount of the photosensitive organic insulating material composition.
5. The photosensitive organic insulating material composition according to any one of claims 1 to 4, wherein, The total amount of the chalcone compounds is 0.1% to 15% by mass relative to 100% by mass of the total amount of the photosensitive organic insulating material composition.
6. The photosensitive organic insulating material composition according to any one of claims 1 to 5, wherein it has a peak in the absorption spectrum in the wavelength range of 300 to 370 nm.
7. An insulating film, which is a photocured product of the photosensitive organic insulating material composition according to any one of claims 1 to 6.
8. A gate insulating film, which is a photocured product of the photosensitive organic insulating material composition according to any one of claims 1 to 6.
9. A transistor having the gate insulating film of claim 8.
10. An electronic device having the transistor of claim 9.
11. A method for manufacturing a gate insulating film, comprising: The process of coating the photosensitive organic insulating material composition according to any one of claims 1 to 6 onto a substrate; and The process of curing the photosensitive organic insulating material composition by exposure to form a gate insulating film.
12. A method for manufacturing a transistor, specifically a method for manufacturing a transistor having a gate insulating film. The method includes the step of forming the gate insulating film using the manufacturing method of the gate insulating film according to claim 11.